The crimson conundrum: heme toxicity and tolerance in GAS - Sachla, Ankita J.; Le Breton, Yoann; Akhter, Fahmina; McIver, Kevin S.; Eichenbaum, Zehava (Frontiers in Cellular and Infection Microbiology, 2014)
The massive erythrocyte lysis caused by the Group A Streptococcus (GAS) suggests that the β-hemolytic pathogen is likely to encounter free heme during the course of infection. In this study, we investigated GAS mechanisms for heme sensing and tolerance. We compared the minimal inhibitory concentration of heme among several isolates and established that excess heme is bacteriostatic and exposure to sub-lethal concentrations of heme resulted in noticeable damage to membrane lipids and proteins. Pre-exposure of the bacteria to 0.1 μM heme shortened the extended lag period that is otherwise observed when naive cells are inoculated into heme-containing medium, implying that GAS is able to adapt. The global response to heme exposure was determined using microarray analysis revealing a significant transcriptome shift that included 79 up regulated and 84 down regulated genes. Among other changes, the induction of stress-related chaperones and proteases, including groEL/ES (8x), the stress regulators spx (5x) and ctsR (3x), as well as redox active enzymes were prominent. The heme stimulon also encompassed a number of regulatory proteins and two-component systems that are important for virulence. A three-gene cluster that is homologous to the pefRCD system of the Group B Streptococcus was also induced by heme. PefR, a MarR-like regulator, specifically binds heme with stoichiometry of 1:2 and protoporphyrin IX (PPIX) with stoichiometry of 1:1, implicating it is one of the GAS mediators to heme response. In summary, here we provide evidence that heme induces a broad stress response in GAS, and that its success as a pathogen relies on mechanisms for heme sensing, detoxification, and repair.